Assessing Medication Adherence at a Student-Run Free Clinic in the Midwest - Jessica Grimmond; Alex Maben; Kalika Mahato; Jenenne Geske; Melanie Menning (Journal of Student-Run Clinics, 2023)
Background: One of the primary barriers to medication adherence is traversing a physical distance to a pharmacy to pick-up medications. There are few studies that have examined how socioeconomic factors affect patient medication adherence in the context of student-run free clinics (SRFC).  Low medication adherence leads to poorer patient outcomes, especially in patients with chronic diseases.Methods: This retrospective chart review aims to quantify the rate of medication adherence at this student-run free clinic using prescription pick-up rate and medication possession ratio (MPR). This study involved review of medication documentation in the electronic medical record (EMR) and charge reports of dispensed medications from the clinic’s community partner, OneWorld pharmacy. Prescriptions written for and picked up by Student Health Alliance Reaching Indigent Needy Groups (SHARING) patients between January 1, 2018, and May 31, 2020, were included for analysis. Medication adherence was calculated using MPR.Results: 1,396 prescriptions were written for 37 patients over the study period and 177 prescriptions (12.7%) were dispensed. The MPR for the patient population is 0.1128 (Standard Deviation (SD) = 0.36159). It took patients an average of 29.4 days (SD = 44.3) to pick-up medications after the prescription was sent.Discussion: At an off-campus pharmacy, SRFC patients had a low prescription pick-up rate and low medication adherence, with delayed time to prescription pick-up. Further investigations are needed to identify barriers to prescription adherence and improve adherence rates.